Biodiversity and environment : proceedings of the National Seminar on Environmental Biology, April 3-5, 1998 - National Seminar on Environmental Biology (1998 : Department of Zoology, Visva Bharati University); Aditya, A. K.; Haldar, P.; Visva-Bharati. Department of Zoology (Delhi : Daya Pub. House, 2000)
In the Indian context.
Seminar held at Department of Zoology, Visva Bharati University, Santiniketan.
Includes bibliographical references.
Keywords: Biodiversity -- India; Biodiversity conservation -- India